ANALISIS PENERAPAN TRANSAKSI MURABAHAH PADA PT. BANK PEMBIAYAAN RAKYAT (BPR) SYARIAH GEBU PRIMA MEDAN - Zulia Hanum (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2014)
Islamic bank is a bank that refers to the procedures for the operation of the provisions of the Al-Quran and Al-Hadith as a source of Islamic law. For the Indonesian economy, Islamic banks boom started in 1997 when the financial crisis occurred. Although Islamic banks have existed in Indonesia in 1992. Monetary crisis is a positive impact on the growth of Islamic banking in Indonesia because reality shows banks operating with Islamic principles can survive amid volatility in exchange rates and high interest rates at that time.The research was conducted at PT. BPR Syariah Gebu Prima Medan. The purpose of this study is to analyze the suitability of the application of the system of financing murabahah transactions PT. BPR Syariah Gebu Prima Medan and analyze the recognition and measurement of revenue murabahah transactions PT. BPR Syariah Gebu Prima Medan with PSAK 102. This research is descriptive qualitative. While the data source is a source of primary data collected directly and secondary data obtained from documents provided by the company.From these results it can be concluded that the application of the system of financing murabahah transactions and income measurement murabahah transactions are implemented by PT. BPR Syariah Gebu Prima Medan in accordance with PSAK 102.